Import Competition and the Great U.S. Employment Sag of the 2000s - Daron Acemoglu; David H. Autor; David Dorn; Gordon H. Hanson; Brendan Price (Center for Economic Studies and ifo Institute (CESifo), 2015)
Even before the Great Recession, U.S. employment growth was unimpressive. Between 2000 and 2007, the economy gave back the considerable employment gains achieved during the 1990s, with a historic contraction in manufacturing employment being a prime contributor to the slump. We estimate that import competition from China, which surged after 2000, was a major force behind both recent reductions in U.S. manufacturing employment and—through input-output linkages and other general equilibrium channels—weak overall U.S. job growth. Our central estimates suggest job losses from rising Chinese import competition over 1999 through 2011 in the range of 2.0 to 2.4 million.
Keywords: F16; J21; 330; trade flows; labor demand